Analisis Penyerapan Tenaga Kerja Pada Sektor Industri Besar dan Sedang Se-Eks Karesidenan Surakarta Tahun 2006-2013 - Prastyaningsih, Arum, Drs. Yuni Prihadi U., M.M (2016)
This study attempts to analyze the production values, the number of business unit, minimum wage, PDRB (Regional Gross Domestic Product) the industrial sector of employment in the medium and large for years 2006-2013 in Karesidenan Surakarta. The analysis using data regression panel. Panel data is a combination of cross place which includes seven areas in Surakarta and time series for eight years  56 observation. The research results show that random effect method (REM) is the best panel data regression model. Based on the unison, get the result that in extent of signification 0.05 value production, the number of units business, minimum wage, and regional domestic product its gross the industrial sector have an impact on employment in the large and medium industrial sector. Based on the validity of influence, the production it has some positive effects significantly to employment of with the 0.504, the number of business unit it has some positive effects significantly to employment of with the 0.199, the minimum wage have negative effects significantly to employment of with the -0.671, while PDRB (Regional Gross Domestic Product) the industrial sector it has some positive effects significantly to employment of with the 0.436